PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 25 BAGAN MELIBUR - Mira Sepriana Septiana; Elfis Suanto Suanto; Yenita Roza Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was based on the mathematics learning outcomes of students at class III SDN 25 Bagan Melibur. There were only 13 of 24 students (54,17%) who achieve the Mastery Minimum Criteria on topic about using the measuring tool in problem solving and the learning process is still teacher centered. This research is action research which aims to increase the mathematics learning outcomes of students at class III SDN 25 Bagan Melibur through the implentation of cooperative learning in type student team achievement division (STAD). The subject is 24 students at class III SDN 25 Bagan Melibur which consist of 10 boys and 14 girls with the heterogenous ability level. The instruments of data collection were observation sheets and test of mathematic learning outcomes. The observation sheets were analyzed in qualitative desciptive, while the test of mathematic learning outcomes was analyzed in quantitative descriptive. The qualitative descriptive showed that there is an improvement of the previous learning process to the first and second cycle. The result showed an increasing number of students who achieve the Mastery Minimum Criteria from the basic score with the percentage 54,17% to 75% on the first daily test and 83,33% on the second daily test. Based on that result, it can be concluded that the implentation of Cooperative Learning in type student team achievement division (STAD) can improve the mathematics learning outcomes of students at class III SDN 25 Bagan Melibur on second semester academic year 2014/2015. Key Words : The mathematics learning outcomes of students, Cooperative Learning in type student team achievement division (STAD), Classroom Action Research.